SEBUAH FENOMENA BERNAMA FACEBOOK: MELIHAT FACEBOOK SEBAGAI MEDIA BARU PEMASARAN - , Muhammad Faried Ismunandar ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Facebook is a phenomenon. Up to now there is no medium that can attract so many people to sign up like facebook. More to it, facebook did it in a relatively short time. Today more than 700 million accounts in facebook from all over the world. Indonesia is the second biggest facebook users in the world. This comes to a surprise as internet penetration is considered to be low in this country. But the need to be able to access facebook is so high among Indonesian, shown in one study that reveals 9 out of 10 internet users in Indonesia are in facebook. That big number of users make facebook a very attractive medium for companies to use it as a marketing tool. But, different from other traditional media like newspaper or TV, facebook has its own characteristic. As a social media, facebook can give access to its users to communicate in many ways. Users in this case are active, where information can be received, erased, responded or shared as each user wish to do. In a way the number of users and its social media characteristic make facebook a powerful marketing tool. But in other way, companies have to be prepared to face reality when their products or services will get negative feedback from customers. With those given conditions, the question would be, whether facebook is the right marketing tool to use. This study try to look it from marketer â brand owner â and expert perspective to answer that question. Reference for this study is from Mangold and Faulds (2009), that the role of social media in an effective marketing communication is as a tool for brand to talk to customers and the platform that enable cutomers to talk to other customers. The answer is yes facebook is the right media as long as it is well managed. Communication from companies to customers is very powerful since the size of facebook users, while the ability for customers to make a communication can be used as a good insight for the companies.